Mixed-mode interaction membrane chromatography for protein fractionation - Nur Farahain, Khusnun (2012)
Nowadays, membrane chromatography has widely use in protein separation. Most of the membrane chromatography is prepared through a chemical modification which sometimes can changes the structure and properties of the membrane itself. In this study, membrane chromatography was prepared through physical modification using the mixed matrix membrane preparation concept. Amberlite IR120 cation exchange resin (CEX) and Lewatit MP500 anion exchange resin (AEX) was used to formulate mixed mode interaction membrane chromatography (MMIMC) based on ethylene vinyl alcohol base membrane matrix. The total resin loading from 20-50% and the ratio between anion exchange resin and cation exchange resin was studied. This research found the optimum resin loading is 30%. Pure AEX MMM has the binding capacity of 340.26 mg BSA/g membrane and pure CEX MMM has a binding capacity of 3166.22 mg LZY/g membrane. The MMIMC with ratio CEX/AEX equal to 50/50 has a capacity of 895.898 mg LZY/g membrane and 3430.74 mg BSA/g membrane. A high performance MMIMC can be produced by optimization the loading percentage of ion exchanger resin and the ratio of CEX/AEX resin incorporate into the membrane.